TINJAUAN YURIDIS PENGATURAN ALAT BUKTI KETERANGAN AHLI DALAM PROSES PEMERIKSAAN PERSIDANGAN PIDANA - Eben Ezer DS; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Expert information is a statement given by someone who has special expertise about what is needed to make the light of a criminal case for the purpose of examination. This is justified in the Criminal Procedure Code Article 1 point 28 and is recognized as a legitimate evidence of five evidences that can be used in the process of criminal evidence stipulated in Article 184 paragraph (1). This evidence was presented to assist the judge in building his conviction before making a decision on the defendant in analyzing any facts that were presented in the process of investigation and examination of the trial. However, the regulation of expert information in the Criminal Procedure Code has not yet arranged in a comprehensive and comprehensive manner regarding the criteria and expert qualifications that can be presented, so that the implications for broad interpretation by the parties who present experts and the reality raises problems in criminal trials specifically for judges in making decisions. The purpose of writing this thesis, namely: First, To determine the arrangement of expert information in the Criminal Procedure Code compared to other legislation. Second, to find out the practice of providing evidence of expert testimony in the reality of criminal trials.This type of research can be classified as a type of normative legal research. This research is descriptive, namely a study that describes clearly and in detail about the regulation and reality of giving expert information in criminal proceedings. Data sources used secondary data consisting of primary legal material, legal material secondary, and tertiary legal materials, data collection techniques in this study with the library study method, after the data collected is then analyzed to draw conclusions.From the results of the research and discussion it can be concluded that, First, the arrangement of expert information in the KUHAP has not been fully and comprehensively regulated so that it requires improvement with references from other laws and regulations. Second, the practice of providing evidence of expert testimony in the reality of criminal proceedings has been presented by both parties in litigation. However, each expert is heavy / lame with the interests of the party that presents it. In the end each statement will give confusion to the judge.Keywords: Evidence Tools - Expert Information - Qualifications - Criminal Investigation and Trial Process.